Open Speech Platform: Democratizing Hearing Aid Research - Sengupta, Dhiman; Boothroyd, Arthur; Zubatiy, Tamara; Yalcin, Cagri; Hong, Dezhi; Hamilton, Sean K; Gupta, Rajesh; Garudadri, Harinath (International Conference on Pervasive Computing Technologies for Healthcare (Print), 2020)
Hearing aids help overcome the challenges associated with hearing loss, and thus greatly benefit and improve the lives of those living with hearing-impairment. Unfortunately, there is a lack of adoption of hearing aids among those that can benefit from hearing aids. Hearing researchers and audiologists are trying to address this problem through their research. However, the current proprietary hearing aid market makes it difficult for academic researchers to translate their findings into commercial use. In order to abridge this gap and accelerate research in hearing health care, we present the design and implementation of the Open Speech Platform (OSP), which consists of a co-design of open-source hardware and software. The hardware meets the industry standards and enables researchers to conduct experiments in the field. The software is designed with a systematic and modular approach to standardize algorithm implementation and simplify user interface development. We evaluate the performance of OSP regarding both its hardware and software, as well as demonstrate its usefulness via a self-fitting study involving human participants.